Commentary: tegaserod and IBS, two decades on. Issue 1 (18th December 2019) - Vakil, Nimish
Abstract : THIS IS A SPECIAL COMMENTARY ON " TEGASEROD, A 5‐HT4 RECEPTOR PARTIAL AGONIST, RELIEVES SYMPTOMS IN IRRITABLE BOWEL SYNDROME PATIENTS WITH ABDOMINAL PAIN, BLOATING AND CONSTIPATION " BY MÜLLER‐LISSNER, S.A., FUMAGALLI, I., BARDHAN, K.D., PACE, F., PECHER, E., NAULT, B., AND RÜEGG, P., ORIGINALLY PUBLISHED IN AP&T IN 2008. DOI:10.1046/J.1365-2036.2001.01094.x